Mercado de la mermelada de maracuyá en Colombia: Una Mirada al Entorno 2015 – 2019, conllevando al reconocimiento de Ventajas Competitivas, como Oportunidad de Diversificación en la Negociación con el Mercado Europeo (2021)
Colombia is a tropical country, with an agricultural vocation, with climatic zones for the development of crops (Pro Colombia, 2016). In this sense, the objective was focused on characterizing the passion fruit jam market in Colombia, taking the 2015-2019 period as a reference, through a market pre-selection matrix, identifying and assessing criteria to objectively select those countries most favorable for internationalization that are dimensioned in the bilateral agreement between Colombia and the European Market. The method was deductive, quantitative, with a documentary historical approach, supported by the tracking of official pages such as the Trade Map, Procolombia, allowing obtaining information data in relation to the variables, in order to recognize opportunities, highlighting relevant aspects related to the five forces until reaching the final stage to identify competitive advantages in business relationships that allow future use of businesses with passion fruit jam.